2006
DOI: 10.1890/0012-9658(2006)87[1637:cihfup]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hardwood Forest Understory Plant Communities in Response to European Earthworm Invasions

Abstract: European earthworms are colonizing earthworm-free northern hardwood forests across North America. Leading edges of earthworm invasion provide an opportunity to investigate the response of understory plant communities to earthworm invasion and whether the species composition of the earthworm community influences that response. Four sugar maple-dominated forest sites with active earthworm invasions were identified in the Chippewa National Forest in north central Minnesota, USA. In each site, we established a 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
218
5
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(241 citation statements)
references
References 52 publications
(89 reference statements)
13
218
5
5
Order By: Relevance
“…Third, forests with heavy Lumbricus invasions are perceived by Ovenbirds to be sub-optimal habitat and are avoided in favor of less impacted areas. In agreement with this hypothesis, Ovenbirds are known to select territories and nest sites with deep leaf litter (Van Horn and Donovan 1994;Mattsson and Niemi 2006) and at least some herbaceous ground cover and shrubs for nest concealment (James 1971;Smith and Shugart 1987), conditions that are characteristic of Lumbricus-free and lightly invaded forests (Hale et al 2006;Holdsworth et al 2007a;Nuzzo et al 2009). All three hypothesized mechanisms could mediate Lumbricus-associated declines; however, further research is required to determine the importance of each.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Third, forests with heavy Lumbricus invasions are perceived by Ovenbirds to be sub-optimal habitat and are avoided in favor of less impacted areas. In agreement with this hypothesis, Ovenbirds are known to select territories and nest sites with deep leaf litter (Van Horn and Donovan 1994;Mattsson and Niemi 2006) and at least some herbaceous ground cover and shrubs for nest concealment (James 1971;Smith and Shugart 1987), conditions that are characteristic of Lumbricus-free and lightly invaded forests (Hale et al 2006;Holdsworth et al 2007a;Nuzzo et al 2009). All three hypothesized mechanisms could mediate Lumbricus-associated declines; however, further research is required to determine the importance of each.…”
Section: Discussionmentioning
confidence: 89%
“…All of the following analyses were repeated for: (1) all forest types combined (n = 124), and (2) points in sugar maple and sugar maple/basswood forests (hereafter; maple-basswood, n = 53), because earthworm effects in the study region have been documented to be most substantial in these forest types (Hale et al 2006;Holdsworth et al 2007a, b), and a previous study found significant associations between Lumbricus and songbirds in these forest types (Loss and Blair 2011). We used independent samples t-tests to compare density of each bird species, as well as litter depth, ground cover, and sedge cover, between Lumbricusfree and invaded sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations